Effect of oxide layer modification of CoCr stent alloys on blood activation and endothelial behavior. Issue 3 (26th June 2014) - Milleret, Vincent; Ziogas, Algirdas; Buzzi, Stefano; Heuberger, Roman; Zucker, Arik; Ehrbar, Martin
Abstract: CoCr alloys, in particular MP35N and L605, are extensively used in biomedical implants, for example for coronary stents. In practice, these alloys present a moderately hydrophobic surface which leads to significant platelet adhesion and consequently to risk of early thrombosis or in‐stent restenosis. Surface modification of biomedical implants is known to alter their biological performances. In this study we focused on the alteration of in vitro biological responses of human cells contacting CoCr surfaces with engineered oxide layers. XPS analysis was performed to determine the composition of the oxide layer of differently treated CoCr while the bulk properties were not modified. An extensive characterization of the surfaces was performed looking at surface roughness, wettability and charge. After static exposure to blood, strongly reduced platelet and increased polymorphonuclear neutrophil adhesion were observed on treated versus untreated surfaces. Comparisons of treated and untreated samples provide evidence for wettability being an important player for platelet adhesion, although multiple factors including surface oxide chemistry and charge might control polymorphonuclear neutrophil adhesion. The differently treated surfaces were shown to be equally suitable for endothelial cell proliferation. We herein present a novel approach to steer biological properties of CoCr alloys. By adjusting their oxide layer composition, substrates were generated which are suitable for endothelial cell growth and at the same time show an altered (reduced) blood contact activation. Such treatments are expected to lead to stents of highly reproducible quality with minimal thrombogenicity and in‐stent restenosis, while maintaining rapid re‐endothelialization after coronary angioplasty. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 629–640, 2015.